AB0191 Sdai as predictor of 1-year efficacy of the first tnf blocker in clinical practice. (23rd January 2014) - Talotta, R.; Atzeni, F.; Battellino, M.; Ditto, M. C.; Batticciotto, A.; Santandrea, S.; Sarzi-Puttini, P.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic disabling autoimmune disease that affects the peripheral synovial joints. The new biological therapies have led to clinical improvements, but about 30% of patients discontinue treatment within the first year. Many studies (mainly based on national registries) have tried to identify variables to predict survival on biological therapy. High baseline HAQ or DAS 28 scores seem to be related to worse outcomes, but no definite variable can predict if or when a patient will be switched to another biological agent. Objectives: To evaluate which of DAS28, CDAI and SDAI is more predictive of the discontinuation of a first TNF blocker within one year. Methods: The variables considered were age at the start of therapy, gender, comorbidity, disease duration, RF positivity, DAS28, CDAI and SDAI scores, the number of previous DMARDs, the concurrent use of MTX and corticosteroids, the anti-TNF agents, the number of tender and swollen joints, functional class, the ESR, and C-RP levels. We compared the relative risk (OR) of switching to another biological agent within the first 12 months in patients in remission, and in those with low, medium or severe disease activity after three and six months. Results: We collected information from the clinical records of 51 patients with RA according to the 1987 ACR criteria (41 F; mean age 56.5 ± 13.5 years, mean disease duration 15.3 + 8.5 years). Rheumatoid factor was positive in 36 patients and anti-CCP antibodies in 33 patients. Forty-one patients were concomitantly treated with MTX 5-20 mg/week, three with leflunomide 20 mg/day, five with hydroxychloroquine 200-400 mg/day, one with sulfasalazine 1500 mg/day, and 32 with prednisone 2.5-10 mg/day. Twelve subjects were treated with ETN 50 mg/week as the first biological agent, 20 with ADA 40 mg every other week, and 27 with IFN 3 mg/kg every eight weeks. Disease activity at the different times of evaluation is shown in Table I . Thirty-four patients switched to another biological agent. Twelve discontinued treatment within the first year. The reason for switching was an adverse event in only 4 cases. The SDAI assessment made after six months was the most accurate predictor of switching within 12 months (p=0.002, OR 16.1, 95% CI 1.5-200.7) compared to CDAI (p=0.04, OR 5.1, 95%CI 0.8-40) and DAS28 (p=0.01, OR 7.1, 95%CI 1.2-55). Conclusions: The SDAI at 6 months seems to be most predictive factor when making therapeutic decisions. We suggest that periodic SDAI assessments should be used for RA follow-up in clinical practice. Disclosure of Interest: None Declared